Escravidão, sociedade e economia na Villa Real de São José do Poxim – 1774 a 1854 - Santos, Robson Williams Barbosa dos (2019)
The present work aims at analyzing society, economy and slavery in Vila Real de São José do Poxim. Inserted in the historical context of the sugarcane monoculture and the Pombalino period, in which it aimed to clean up Portugal's deficit economy with the increase of economic activities in Brazil, Sebastião Carvalho e Melo, Marquês de Pombal, determined the creation of companies of commerce such as that of Pernambuco and Paraíba. Within this context, in the middle of the eighteenth century, and extending to the mid-nineteenth century, the village of Poxim was no different from many other regions of northern Brazil, whose social formation and human contingent were born around the mills. The Poxim developed around the Jenipapo and Portion around 1718, both of which would have been important for the transatlantic trade of enslaved. The process of occupying the valley of the Poxim River and, later, the one of Coruripe, was due to the creation of cattle and then to the installation of the first sugar mills in the region. The place appeared there by the 1600s as a point of support for travelers leaving Salvador and headed towards Penedo, Alagoas do Sul, Porto Calvo, Recife and Olinda. These travelers roamed these places on the "waterways" like ponds, streams and rivers. The Poxim River was one of these "waterways", which, interlinked with the São Francisco River and other rivers in the region, stimulated the supply and consumption market for slaves, sugar, salt, cotton, spirits, tobacco and other foodstuffs in the region. valley of the San Francisco. It was also widely used as the driving force of the Jenipapo, Portion, and other engenhos mills. The Vila Real de São José do Poxim counted on the presence of the African for the heavy work in the fields of sugarcane and sugar cane. The black slave, at the same time as the predominant labor force in that rural area, surrounded by the cane fields, was also an anonymous artist, expressing his gift and talent in church-building, in the making of saints and bells, and in urban improvement of the village of Poxim. With this, we observed that the work of the slaves was not limited in the making and the manufacture of sugar. Taking these aspects into account, the study of Vila Real de São José do Poxim is directly related to the genesis of the social formation of Alagoas.